2010
DOI: 10.1080/14772000.2010.508502
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic positions and taxonomic assignments of the systematically controversial genera,Spirotrachelostyla,UroleptopsisandTunicothrix(Protozoa, Ciliophora, Stichotrichia) based on small subunit rRNA gene sequences

Abstract: The phylogenetic positions of three systematically controversial genera of ciliates, Spirotrachelostyla, Uroleptopsis and Tunicothrix, have never been established by molecular data. The small subunit rRNA genes of three species, S. tani, U. citrina and T. wilberti, were sequenced and added to existing sequences of stichotrichs and other ciliates to construct phylogenetic trees. Results indicate the following: (1) Uroleptopsis is most closely related to species of Pseudokeronopsis, supporting its assignment to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…2009a,b; Paiva & Silva‐Neto 2009, Paiva et al. 2009; Huang et al. 2010) have shown that analyses combining morphological and morphogenetic characters with molecular characters are more likely to yield reliable results, especially in some taxonomically confused groups.…”
Section: Introductionmentioning
confidence: 99%
“…2009a,b; Paiva & Silva‐Neto 2009, Paiva et al. 2009; Huang et al. 2010) have shown that analyses combining morphological and morphogenetic characters with molecular characters are more likely to yield reliable results, especially in some taxonomically confused groups.…”
Section: Introductionmentioning
confidence: 99%
“…Their phylogenetic placement results in polyphyly of traditional urostylids in such analyses (e.g. Schmidt et al, 2007;Paiva et al, 2009;Huang et al, 2010;Li et al, 2010a (Berger, 2006), but nevertheless showing the retroextendians to be polyphyletic. This is basically due to the position of Apokeronopsis spp.+Thigmokeronopsis stoecki Shao et al, 2008, away from Pseudokeronopsis spp., a phylogenetic pattern that is consistent with previous studies (e.g.…”
Section: Comparison With Related Speciesmentioning
confidence: 99%
“…To minimize sequence errors, the Ex Taq (TaKaRa, Japan) which shows 4-fold higher fidelity compared with the conventional Taq, with an error rate of about 2.2 × 10 −6 , was used for PCR amplification. The purification of PCR products, cloning and sequencing were performed according to previous reports (Huang et al 2010;Zhang et al 2010). Multiple positive bacterial clones were sequenced for each species.…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%